2010
DOI: 10.1186/1471-227x-10-5
|View full text |Cite|
|
Sign up to set email alerts
|

Involvement in emergency situations by primary care doctors on-call in Norway - a prospective population-based observational study

Abstract: BackgroundPrimary care doctors on-call in the emergency primary health care services in Norway are, together with the ambulances, the primary resources for handling emergencies outside hospitals. There is a lack of reliable data for Norway on how often the primary care doctors are alerted and on their responses in the most urgent emergency cases. The aim of this study was to investigate how doctors on-call are involved in red responses (highest priority), using three different emergency medical communication c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
3
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 10 publications
0
25
3
2
Order By: Relevance
“…Given our findings, it is a paradox that there are EMCCs that seldom alerts GPs, and that GP participation is low [5]. The GPs in casualty clinics have different reasons for not responding to call outs.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Given our findings, it is a paradox that there are EMCCs that seldom alerts GPs, and that GP participation is low [5]. The GPs in casualty clinics have different reasons for not responding to call outs.…”
Section: Discussionmentioning
confidence: 86%
“…The availability of the HEMS is also vulnerable to weather and competing missions [4]. A study of three Norwegian dispatch centers in 2007 found that the HEMS was alerted for approximately 8 percent of the “red responses” [5]. Therefore, pre-hospital emergency medicine in Norway is based on the local ambulance and GP on call, with the HEMS as an important supplement [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6] A study among EMTs found that they perceived themselves as being more competent than others in handling prehospital emergencies. [7] GPs were described as being the most problematic occupational group to cooperate with during emergencies.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of the study was to try to obtain a better understanding of why duty doctors in the municipal health service do not always participate in emergency call-outs (9,10). Because the study is qualitative and not intended for generalisation, the findings cannot simply be transferred to other accident and emergency doctors.…”
Section: Discussionmentioning
confidence: 99%